Silica gel microfibres by electrospinning for adsorption chillers. (15th November 2019) - Freni, A.; Calabrese, L.; Malara, A.; Frontera, P.; Bonaccorsi, L.
Abstract: Silica gel is one of the most used porous material in commercial water adsorption chillers for the low cost and large market availability. In most applications, silica gel is used as granules with limitation in heat transfer efficiency and material hydrothermal stability. In this work, preliminary results of a new hybrid coating made of microfibres obtained by the electrospinning of silica gel/polymer solutions are presented. Polyacrylonitrile (20 wt%) and different silica gel powders (80 wt%) were mixed and electrospun to produce fibrous coatings on aluminium surfaces. Thermal analysis of the hybrid microfibres by TGA-DSC showed that the coating was stable up to T = 290 °C with no evidence of thermal degradation of the microfibres. Measurements of water adsorption isobars of silica gel microfibres at P = 11 mbar and P = 42 mbar showed that the water adsorbed was 80 wt% of the water uptake capability of the original silica gel demonstrating that the polymeric component of microfibres did not occluded the adsorbing material porosity. Highlights: A new silica gel coating for adsorption chillers is presented. The coating is made of electrospun microfibres of 80 wt% silica gel and 20 wt% polyacrylonitrile. The microfibres coating has shown thermal stability up to 290 °C. The water uptake along a typical cooling cycle plotted on coating isobars, (11–42 mbar), resulted > 10 wt%.